Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1128/aac.00004-15
|View full text |Cite
|
Sign up to set email alerts
|

Etest Cannot Be Recommended for In Vitro Susceptibility Testing of Mucorales

Abstract: e Amphotericin B and posaconazole susceptibility patterns were determined for the most prevalent Mucorales, following EUCAST (European Committee on Antimicrobial Susceptibility Testing) broth microdilution guidelines. In parallel, Etest was performed and evaluated against EUCAST. The overall agreement of MICs gained with Etest and EUCAST was 75.1%; therefore, Etest cannot be recommended for antifungal susceptibility testing of Mucorales. Amphotericin B was the most active drug against Mucorales species in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…117,118 In addition, a recent study reported poor overall agreement between Etest and EUCAST MICs for amphotericin B and posaconazole (75.1%) when used to measure activity against members of the order Mucorales, the causative agents of mucormycosis, and recommended that the Etest assay not be used against these fungi. 119 The quality and reliability of Etest MIC results may also be influenced by operator technique in applying the strips as well as the trailing affect that may be observed with the azoles against some yeast species. Similar to what has been observed with the YeastOne colorimetric assay, 1 study has also reported a high incidence of C glabrata and C krusei isolates with intermediate caspofungin MICs with this assay.…”
Section: Commercially Available Antifungal Susceptibility Assaysmentioning
confidence: 99%
“…117,118 In addition, a recent study reported poor overall agreement between Etest and EUCAST MICs for amphotericin B and posaconazole (75.1%) when used to measure activity against members of the order Mucorales, the causative agents of mucormycosis, and recommended that the Etest assay not be used against these fungi. 119 The quality and reliability of Etest MIC results may also be influenced by operator technique in applying the strips as well as the trailing affect that may be observed with the azoles against some yeast species. Similar to what has been observed with the YeastOne colorimetric assay, 1 study has also reported a high incidence of C glabrata and C krusei isolates with intermediate caspofungin MICs with this assay.…”
Section: Commercially Available Antifungal Susceptibility Assaysmentioning
confidence: 99%
“…The Mucorales strain sets used to evaluate the performance of the rnl marker given in Tables S1 and S2 were characterized in a previous study [18]. Fungal stocks stored in 0.9% sodium chloride at −20 • C served as inoculum sources.…”
Section: Strain Collection and Cultivationmentioning
confidence: 99%
“…Identification (ID) at the genus level was performed by visualization of microscopic (Olympus CX21 microscope; Olympus, USA) and macroscopic (Axioplan microscope; Zeiss, Germany) characteristics. Species ID was obtained by direct sequencing of the internal transcribed spacer (ITS) [20] with slightly modified primers [18]. Genomic DNA was extracted [21] and ITS sequences were identified using the pairwise sequence alignment tool of the central bureau schimmelcultures (CBS) Knaw database (http://www.cbs.knaw.nl/Collections).…”
Section: Strain Collection and Cultivationmentioning
confidence: 99%
“…other members of the Mucorales, which could be due to the ignorance regarding the two varieties in the past (Caramalho et al, 2015).…”
Section: S Dolatabadi and Othersmentioning
confidence: 99%
“…The choice of antifungal agents used differs widely between various mucoralean fungi at species or even variety level; e.g. amphotericin B shows different activities against Rhizopus microsporus and Rhizopus arrhizus, thus confirming different susceptibility patterns between species or even varieties of mucoralean fungi (Chowdhary et al, 2014;Caramalho et al, 2015).…”
Section: Introductionmentioning
confidence: 99%